The influence of pressure on the structure and dynamics of hydrogen bonds in zoisite and clinozoisite - Winkler, B.; Gale, Julian; Refson, K.; Wilson, D.; Milman, V. (Springer-Verlag, 2008)
Density functional theory calculations have been used to study the pressure-induced changes of the hydrogen bond of Fe-free orthozoisite and clinozoisite and the concomitant shifts of the OH-stretching frequencies. Two independent parameter-free lattice dynamical calculations have been employed. One was based on a planewave basis set in conjunction with norm-conserving pseudopotentials and a density functional perturbation theory approach, while the other used a localised basis set and a finite displacement algorithm for the lattice dynamical calculations. Both models confirm the unusually large pressure-induced red-shift found experimentally ( 33.89 cm 1/GPa) in orthozoisite, while the pressureinduced shifts in clinozoisite are much smaller ( 5 to 9 cm 1/GPa). The atomistic model calculations show that in orthozoisite the nearly linear O H_O arrangement is compressed by about 8% on a pressure increase to 10 GPa,while concomitantly the O H distance is significantly elongated (by 2.5% at 10 GPa). In clinozoisite, the O H_O arrangement is kinked \OHO 166 at ambient conditions and remains kinked at high pressures, while the O-H distance is elongated by only 0.5% at10 GPa. The current calculations confirm that correlations between the distances and dynamics of hydrogen bonds, which have been established at ambient conditions, cannotbe used to infer hydrogen positions at high pressures.